(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article is devoted to an urgent topic in legal science. The change in the economic situation in our country, caused by a number of significant factors, has led to the fact that the ability to pay of citizens has sharply decreased. We believe that a financing agreement for the assignment of financial claims represents a worthy alternative to resolve such a problem. This article analyzes the ways of applying the contract for the assignment of a monetary claim. The risks in economic terms are considered when applying this method in practice.